Redistribution in Switzerland: Social Cohesion or Simple Smoothing of Lifetime Incomes? - Monika Engler (Swiss Journal of Economics and Statistics, 2011)
Using the example of Switzerland, this paper examines the extent to which the state and the social security institutions change the income distribution. Two sets of questions are examined: (1) Who benefits from the public services, and who bears the public costs? (2) To what extent does an annual redistribution involve redistribution (a) across households with different lifetime income, and (b) across different phases of life within the same households? Budget incidence analyses and pseudo panel procedures allow to compare annual and lifetime household incomes that arise before and after transfers. The results suggest that public interventions induce substantial redistribution, which is due primarily, however, to income-smoothing transfers within households and not to redistribution across households.
Keywords: D31; D91; H22; 330; Budget Incidence Analysis; Redistribution; Lifetime Income Smoothing; Pseudo Panel Procedure